An investigation of chlorbutol in ophthalmic and parenteral solutions - Summers, Robert Stanley (Rhodes University, Faculty of Pharmacy, Pharmacy, 1967)
From Introduction Chlorbutol , which is tri-chlor-tertiary-butanol, was first prepared by Willgerodt in 1886 (1). The reaction he used for its preparation is still used today, though slightly modified (2)(3)(4), and is suggested by its original name "acetone-chloroform". The substance was prepared by adding solid potassium hydroxide to a cold mixture of acetone and chloroform (5 ). Chlorbutol is a derivative of the trichlorinated derivative of methane, and its formation may best be described by the use of structural formulae.
Keywords: Parenteral solutions; Solutions (Pharmacy); Ocular pharmacology